Sarcoidosis with bone involvement mimicking metastatic disease at (18)F-FDG PET/CT: problem solving by diffusion whole-body MRI - Conte, Giorgio (Ecancermedicalscience, 2015)
Bone involvement has been reported in 1–13% of patients with sarcoidosis. Both 18F-fluorodeoxyglucose ((18)F-FDG) Positron Emission Tomography/Computed Tomography (PET/CT) and conventional magnetic resonance imaging (MRI) are sensitive in detecting sarcoidosis bone lesions, but are not always reliable in differentiating sarcoidosis bone lesions from metastatic disease, thus often requiring bone biopsy. We describe the use of diffusion whole-body MRI for bone assessment in a patient with breast cancer and sarcoidosis, presenting with bone marrow lesions mimicking metastatic disease at (18)F-FDG PET/CT. In our case, diffusion whole-body MRI represented a useful tool for bone assessment and overcame the limitation of (18)F-FDG PET/CT in discriminating inflammatory bone marrow involvement from metastatic disease.